MDCT evaluation of aortic root and aortic valve prior to TAVI. What is the optimal imaging time point in the cardiac cycle? - Jurencak, Tomas (Eur Radiol, 2015)
OBJECTIVES: To determine the optimal imaging time point for transcatheter aortic valve implantation (TAVI) therapy planning by comprehensive evaluation of the aortic root. METHODS: Multidetector-row CT (MDCT) examination with retrospective ECG gating was retrospectively performed in 64 consecutive patients referred for pre-TAVI assessment. Eighteen different parameters of the aortic root were evaluated at 11 different time points in the cardiac cycle. Time points at which maximal (or minimal) sizes were determined, and dimension differences to other time points were evaluated. Theoretical prosthesis sizing based on different measurements was compared. RESULTS: Largest dimensions were found between 10 and 20 % of the cardiac cycle for annular short diameter (10 %); mean diameter (10 %); effective diameter and circumference-derived diameter (20 %); distance from the annulus to right coronary artery ostium (10 %); aortic root at the left coronary artery level (20 %); aortic root at the widest portion of coronary sinuses (20 %); and right leaflet length (20 %). Prosthesis size selection differed depending on the chosen measurements in 25–75 % of cases. CONCLUSION: Significant changes in anatomical structures of the aortic root during the cardiac cycle are crucial for TAVI planning. Imaging in systole is mandatory to obtain maximal dimensions. KEY POINTS: • Most aortic root structures undergo significant dimensional changes throughout the cardiac cycle. • The largest dimensions of aortic parameters should be determined to optimize TAVI. • Circumference-derived diameter showed maximum dimension at 20 % of the cardiac cycle.